Project-Based Learning and Active Learning in Creating BIPA Material to Bolster SDGs - Mayrita, Hastari; Indah Sari, Ayu Puspita; Yanti, Cita Hikmah; Suardi, M; Rahmi Pratiwi, Annisa (Indonesian Research Journal in Education |IRJE|, 2024)
This study aimed to explore the effectiveness of collaborative Project-Based Learning (PJBL) and active learning in the BIPA (Indonesian for Foreign Speakers) course, which could serve as a promotional medium for the BIPA program to support the achievement of SDG Quality Education. The method used was classroom action research with a mixed method involving two learning cycles. The study participants were students from the Indonesian Education Study Program who took the BIPA course. The findings show collaboration between these two learning models successfully enhanced student engagement, creativity, and learning outcomes quality. The results in the form of drafts of BIPA teaching materials developed by the students showed good quality. At the same time, the project helped build collaboration, communication, and creativity, which supported SDG Industry, Innovation, Infrastructure, and SDG Peace and Justice through cultural diplomacy and promotion of the Indonesian language at the international level.